Digitalization of SMEs to Survive Amid The Pandemic - Purba, Abdul Rahman Sutara; Balqiah, Tengku Ezni (Jurnal Manajemen Indonesia, 2024)
The purpose of the research conducted was to understand the relationship of internal factors of SME digitalization on the company's financial performance during the pandemic to test 5 hypotheses. This study used a survey method, questionnaires to get respondents' answers. A purposive technique was used and managed to collect 359 respondents who had small to medium medium-scale businesses. Furthermore, the research model was tested statistically with PLS-SEM analysis techniques. Based on the results of data processing and analysis, it is proven that all hypotheses are acceptable, which shows that the internal factors of digitalization of SME companies, namely information and technology, employee skills, and digital strategies, have a positive and significant effect on the digitalization of SME companies. Furthermore, digitalization affects the company's financial performance where employee skills have the largest variable of the three factors. Digitalization is able to mediate the influence of information and technology, employee capabilities, and digital strategies on the financial performance of SMEs. This result shows that digitalization is also important, especially during a pandemic where SMEs must adapt to technology so that they can survive by maintaining their business performance. These findings add to the empirical development of literature on SME digitization factors such as information and technology, employee skills, and digital strategies. In addition, this study also provides an understanding of how much influence these three factors can affect the digitalization of SMEs. Keywords— Digitalization; Employee Skill; Financial Performance; Information and Technology; SMEs